Reprint. From: portfolio "60. Jahrestag der Novemberrevolution/60. Jahrestag der Gründung der KPD". Poster consists of 3 parts - Segner, Klaus, (1968)
Reprint. From: portfolio "60. Jahrestag der Novemberrevolution/60. Jahrestag der Gründung der KPD". Poster consists of 3 parts.